The magic of a methyl group: Biochemistry at the service of medicine - De Clercq, Erik (Biochemical pharmacology, 2023)
A carbon-carbon linkage is created when a methyl group is implanted on dUMP, thus resulting in the formation of dTMP by thymidylate synthase. The methyl group is deleted by aromatase when androgens are converted to estrogens. The methyl group is rearranged with the help of vitamin B12 in the isomerization of methylmalonyl-CoA to succinyl-CoA. S-adenosylmethionine (SAM) serves as the universal methyl donor involved in the biosynthesis of adrenaline and creatine(phosphate). It also interferes with the 5'-mRNA capping and the degradation of catecholamines (i.e. adrenaline, noradrenaline). Cholesterol could be viewed as a conglomeration of methyl groups. Finally, as part of valine, two methyl functions participate in the origin of one of the most frequent hereditary diseases on earth, sickle cell anemia.
Keywords: Epinephrine; cholesterol; vitamin B 12; Vitamin B 12; Cholesterol; adrenalin